Alumina Support

The alumina support with a controlled pore structure and specific properties enhances catalytic activity and selectivity for dichloroethane production by addressing the issues of reduced surface area and pore volume in conventional supports, while minimizing by-product formation and maintaining stability.

JP7612354B2Active Publication Date: 2025-01-14MIZUSAWA INDAL CHEM LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020134207
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-06
Publication Date
2025-01-14
Estimated Expiration
2040-08-06

AI Technical Summary

Technical Problem

Conventional alumina supports for catalysts face issues of reduced specific surface area and pore volume due to compression molding, leading to decreased adsorption capacity and catalytic activity, while also increasing unwanted side reactions.

Method used

An alumina support with a cylindrical shape and controlled pore structure, featuring a BET specific surface area of 140 to 280 m²/g, total pore volume of 0.04 to 0.15 cm³/g, and macropore volume of 0.02 cm³/g or less, along with a tapping bulk density of 620 to 780 g/L, is developed to enhance catalytic activity and reduce by-product yield.

Benefits of technology

The alumina support achieves high catalytic activity and selectivity for dichloroethane production with reduced by-product formation, despite maintaining high pressure resistance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612354000002
    Figure 0007612354000002
  • Figure 0007612354000003
    Figure 0007612354000003
  • Figure 0007612354000004
    Figure 0007612354000004
Patent Text Reader

Abstract

To provide an alumina carrier to be used for a catalyst for gas phase reaction, highly activating catalytic reaction, and reduced in a yield of by-products, and to provide a gas reaction catalyst carried with a metallic compound on the alumina carrier.SOLUTION: An alumina carrier to be used for a catalyst for gas phase reaction has a cylindrical shape having at least one penetrating hollow hole. The alumina carrier is such that: a BET specific surface area is 140-280 m2 / g; a volume (total pore volume) of pores having a pore diameter of 15 nm or more and 20,000 nm or less, measured by a mercury press-in method is 0.04-0.15 cm3 / g; a volume of pores having a pore diameter of 1,000 nm or more and 20,000 nm or less is 0.02 cm3 / g or less; and a tapping bulk density is 620-780 g / L.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alumina support for use in catalysts for gas phase reactions. [Background technology]

[0002] Alumina supports are widely used as supports for catalysts. Such alumina supports are made of activated alumina having a gamma structure or a structure close to it.

[0003] Alumina carriers are usually obtained by molding and sintering hydrated alumina (aluminum hydroxide) as a raw material. A hollow cylindrical shape is preferred as the shape of the molded body, as it provides a large contact area between the catalyst supported on the carrier and the substance to be treated, and also reduces pressure loss during various operations. Compression molding is preferred as a molding method, as it ensures the strength of the carrier. Patent Document 1 describes a catalyst made of a hollow cylindrical alumina body formed by compression molding. The catalyst is cylindrical in shape, has an outer diameter D of 3 mm to less than 6 mm, an inner diameter of 1.0 mm or more, a wall thickness of 1.5 mm or less, and a height H of 3 to 6 mm, and is particularly suitable as a fixed catalyst for oxyhalogenation reactions or halogenation reactions.

[0004] However, compression molding generally has the problem of reducing the specific surface area and pore volume. That is, if the tableting pressure during compression molding is set to be large, the strength of the resulting alumina compact increases, but at the same time, the mesopores and macropores shrink and the specific surface area tends to decrease, which causes the problem of a significant decrease in the adsorption capacity and activity of the compact.

[0005] Therefore, the present applicant has provided an alumina molded body characterized in that 50 to 95% by weight of the alumina powder is alumina with a γ structure or close to a γ structure, the crushing strength per unit height of the formed alumina-based molded body is 0.30 kg / mm ​​or more, and the peak of the pore distribution in the pore diameter range of 20 to 700 angstroms determined by a nitrogen adsorption method is located at 90 to 150 angstroms (see Patent Document 2). The alumina molded body has a high strength and apparent density, and the adsorptivity and surface activity are maintained at a high level, and the shrinkage of the mesopores that serve as adsorption sites and the macropores that function as introduction spaces for stably introducing the treatment substance to be subjected to the catalytic reaction into the mesopores is also suppressed.

[0006] As shown in Patent Document 2 by the present applicant, it has been conventionally recognized that suppressing the shrinkage of mesopores and macropores is effective for the expression of catalytic activity. In particular, it has been recognized that in order to effectively exert catalytic activity, it is necessary to use an alumina support that sufficiently retains the volume of macropores with a diameter of 1000 nm or more. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 56-141842 [Patent Document 2] JP 2001-226172 A Summary of the Invention [Problem to be solved by the invention]

[0008] Conventional alumina supports with controlled pore structure exhibit high catalytic activity, but also increase undesired unintended activity such as side reactions. There is therefore a demand for an alumina support that can simultaneously increase the activity of the targeted catalytic reaction while suppressing by-products. Therefore, an object of the present invention is to provide an alumina carrier which is used as a catalyst for a gas phase reaction, and which, particularly when a chlorination catalyst such as copper chloride is supported, exhibits high catalytic activity and reduces the yield of by-products. [Means for solving the problem]

[0009] According to the present invention, an alumina carrier used in a catalyst for a gas phase reaction has a cylindrical shape with at least one through-hole and a BET specific surface area of ​​140 to 280 m. 2 / g, and the volume of pores with diameters of 15 nm to 20,000 nm (total pore volume) measured by mercury intrusion porosimetry is 0.04 to 0.15 cm 3 / g, and the volume of the pores having a diameter of 1000 nm or more and 20000 nm or less is 0.02 cm 3 / g or less and a tapping bulk density of 620 to 780 g / L.

[0010] In the alumina support of the present invention, (1) The average compressive strength is 18N or more. (2) The shape is cylindrical with one hollow hole penetrating in the height direction, with an outer diameter of 3 to 6 mm, an inner diameter of 1.0 mm or more, a wall thickness of 1.0 to 2.5 mm, and a height of 3 to 6 mm. (3) To be used as a support for a catalyst in the gas-phase chlorination reaction of ethylene; is preferred.

[0011] The present invention also provides a gas phase reaction catalyst in which one or more metal compounds are supported on the alumina support.

[0012] In the gas phase reaction catalyst of the present invention, it is preferable that copper chloride is supported as the metal compound.

[0013] In the gas phase reaction catalyst of the present invention, the volume of pores having a pore diameter of 15 nm or more and 20,000 nm or less as measured by mercury intrusion porosimetry is 0.04 to 0.15 cm 3 / g, and the volume of pores with a diameter of 1000 nm or more and 20000 nm or less is 0.02 cm 3 It is preferable that the molecular weight is not more than 1 / g.

[0014] The gas phase reaction catalyst of the present invention is preferably used as a catalyst for producing dichloroethane by the gas phase chlorination reaction of ethylene.

[0015] According to the present invention, there is further provided a method for producing the alumina carrier, which comprises using hydrated alumina having at least two particle size distribution peaks in a particle size region of 300 μm or less, mixing the hydrated alumina with a fatty acid metal salt to prepare a molding raw material, and compression molding the molding raw material to obtain a cylindrical body having at least one hollow hole passing therethrough, and calcining the cylindrical body to convert the hydrated alumina into alumina.

[0016] In the method for producing an alumina carrier of the present invention, the hydrated alumina has a median diameter (D 50 ) is 45 to 100 μm, D 10 is 1 to 10 μm, D 90 It is preferable that the thickness is 180 to 400 μm.

[0017] In this specification, the expressions mesopores and macropores are used for convenience of explanation, taking into consideration the relative sizes of pore diameters, and refer to mesopores with a pore diameter of 2 nm or more and less than 50 nm, and macropores with a pore diameter of 50 nm or more and 20,000 nm or less.

[0018] According to the present invention, there is provided a method for producing dichloroethane using the gas phase reaction catalyst of the present invention.

[0019] In the method for producing dichloroethane of the present invention, it is preferable to carry out the reaction of ethylene, hydrogen chloride gas and oxygen at 220° C. to 330° C. in the presence of the catalyst of the present invention.

[0020] According to the present invention, there is provided a method for producing a vinyl chloride monomer, which comprises a step of thermally decomposing the dichloroethane. Effect of the Invention

[0021] A particularly important feature of the alumina carrier of the present invention is that the total pore volume measured by mercury intrusion porosimetry is 0.04 to 0.15 cm 3 / g, and the volume of the pores having a diameter of 1000 nm or more and 20000 nm or less is 0.02 cm 3 / g or less, the ratio of macropores is reduced. In the present invention, the fact that the alumina carrier having the above-mentioned pore structure makes the catalytic reaction highly active and reduces the yield of by-products is a phenomenon found through many experiments, and the reason for this has not yet been clearly elucidated. In particular, this contradicts the recognition that it is necessary to use an alumina carrier that sufficiently retains the volume of macropores with a diameter of 1000 nm or more in order to effectively exert catalytic activity. However, in order to make the catalytic reaction highly active and reduce the yield of by-products, it is necessary to achieve both high catalytic activity and ease of releasing reaction heat. This is because it is believed that the generation of by-products is caused by reaction heat. It is likely that the above-mentioned pore structure achieves a high degree of compatibility between high catalytic activity and ease of releasing reaction heat.

[0022] The gas phase reaction catalyst of the present invention is characterized in that, despite its high pressure resistance, it has high catalytic activity and exhibits extremely high selectivity to dichloroethane (EDC). [Brief description of the drawings]

[0023] [Figure 1] 1 is a graph showing particle size distribution obtained by a laser diffraction / scattering method for hydrated alumina raw materials used in the examples and comparative examples of the present invention. [Diagram 2] 1 is a graph showing particle size distribution obtained by a laser diffraction / scattering method for hydrated alumina raw materials used in the examples and comparative examples of the present invention. [Diagram 3] 1 is a graph showing Log differential pore distribution measured by mercury intrusion porosimetry for Examples 1 to 3 and Comparative Examples 1 to 3 of the present invention. [Figure 4] 1 is a graph showing Log differential pore distribution measured by mercury intrusion porosimetry for Examples 1 to 3 and Comparative Examples 1 to 3 of the present invention. [Diagram 5] FIG. 2 is an enlarged view of a graph of Log differential pore distribution measured by mercury intrusion porosimetry for Examples 1 to 3 and Comparative Examples 1 to 3 of the present invention. [Figure 6] FIG. 2 is an enlarged view of a graph of Log differential pore distribution measured by mercury intrusion porosimetry for Examples 1 to 3 and Comparative Examples 1 to 3 of the present invention. [Figure 7] 1 is a graph showing differential pore distributions measured by a nitrogen adsorption BJH desorption method for Examples 1 to 3 and Comparative Example 1 in the present invention. [Figure 8] 1 is a graph showing differential pore distributions measured by a nitrogen adsorption BJH desorption method for Examples 1 to 3 and Comparative Example 1 in the present invention. [Figure 9] 1 is a graph showing differential pore distributions measured by a nitrogen adsorption BJH desorption method for Examples 1 to 3 and Comparative Example 1 in the present invention. [Figure 10] 1 is a graph showing differential pore distributions measured by a nitrogen adsorption BJH desorption method for Examples 1 to 3 and Comparative Example 1 in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] <Alumina carrier> The alumina carrier of the present invention is not particularly limited in terms of its crystal structure as long as it has a multi-element pore structure described below, and may have a crystal structure such as γ, θ, δ, η, or κ. However, γ-alumina is particularly preferred in that a stable multi-element pore structure can be easily formed.

[0025] In the present invention, the volume of pores having a pore diameter of 15 nm or more and 20,000 nm or less is defined as the total pore volume. The alumina support of the present invention has a multi-component pore structure having mesopores and macropores.

[0026] The alumina support of the present invention has a total pore volume of 0.04 to 0.15 cm 3 / g, preferably 0.06 to 0.11 cm 3 / g. Total pore volume is 0.04 cm 3 If the total pore volume is less than 0.15 cm3 / g, it may be difficult to form a certain amount of mesopores and macropores. 3 If the alumina support has a molecular weight of more than 10000 / g, the heat resistance and compressive strength of the alumina support will be reduced, the performance of the support for supporting a catalytically active component will be impaired, and the pore structure will not be able to be stably maintained due to thermal shrinkage, collapse, etc., and it may become difficult to stably exhibit catalytic performance.

[0027] The alumina carrier of the present invention has a pore volume of 0.02 cm3 or less for macropores having a diameter of 1,000 nm or more and 20,000 nm or less, provided that the total pore volume is within the above range. 3 / g or less, preferably 0.01 cm 3 / g or less, and particularly preferably 0.008 cm 3 In the alumina carrier of the present invention, when the volume of the macropores in the above range is large, the catalytic reaction becomes highly active, but the yield of by-products also tends to increase. 3 If it is greater than 1 / g, there is a risk that the reduction of by-products will be insufficient.

[0028] In the present invention, the total pore volume and the macropore volume are measured by mercury intrusion porosimetry.

[0029] The alumina carrier of the present invention has a high specific surface area in relation to the total pore volume and the volume of macropores having a diameter of 1000 nm or more and 20000 nm or less, which are in the above-mentioned ranges as measured by mercury intrusion porosimetry, and has a BET specific surface area of ​​140 to 280 m as measured by nitrogen adsorption method. 2 / g, preferably 160 to 260 m 2 / g.

[0030] The alumina carrier of the present invention has a tapped bulk density of 620 to 780 g / L, preferably 650 to 750 g / L, determined from the volume and weight of the alumina carrier when packed in a vessel such as a reactor or cylinder and tapped. The tapped bulk density increases with increasing pressure during compression molding. It also varies depending on the firing conditions. If the tapped bulk density is less than 620 g / L, the compressive strength and abrasion strength will be lower than those in the above ranges, and if the tapped bulk density is more than 780 g / L, the density will be high, so the pore volume will be reduced, which may result in a decrease in catalytic reaction activity.

[0031] In the alumina support of the present invention, in a graph of the Log differential pore distribution obtained from the pore volume measured by mercury intrusion porosimetry, the peak apex in the region of pore diameters of 50 nm or more is preferably located in the range of 100 to 1100 nm, more preferably in the range of 300 to 1000 nm. If the peak apex is not located in the range, there is a risk of a decrease in catalytic reaction activity or an increase in the yield of by-products.

[0032] In addition, the alumina support of the present invention preferably does not have a peak in the pore diameter region of 15 to 50 nm in the graph of the Log differential pore distribution. If the alumina support has a peak in this region, the activity of the catalytic reaction may decrease and the yield of by-products may increase.

[0033] In the alumina support of the present invention, the peak apex is preferably located in the range of 3 to 9 nm, more preferably in the range of 4 to 7 nm, in a graph of the differential pore distribution obtained from the pore volume measured by the nitrogen adsorption method. If the peak apex is not located in the range, there is a risk of a decrease in catalytic reaction activity and an increase in the yield of by-products.

[0034] The alumina carrier of the present invention has an average compressive strength of at least 18 N, and preferably at least 20 N. The average compressive strength in the present invention is the load at which the alumina carrier is crushed when the alumina carrier is placed with its side facing down and a load is applied vertically from above, and is the average value of the strengths of 20 randomly selected alumina carriers measured. If the average pressure resistance of the alumina carrier is 18N or more, the average pressure resistance of the catalyst obtained from the alumina alone of the present invention will be equal to or greater than that of the alumina carrier.

[0035] The shape of the alumina carrier of the present invention is a cylinder having one hollow hole penetrating in the height direction. By making it a hollow cylinder, the pressure resistance strength of the molded body is high, the contact area between the molded body and the reactants or treated materials is large, and the pressure loss during various operations is also small. As such a cylindrical shape, from the viewpoints of the above-mentioned pressure resistance, ensuring the contact area, reducing pressure loss, etc., it is preferable that the outer diameter of the circle be 3 to 6 mm, particularly 4 to 5.5 mm, the inner diameter be 1.0 mm or more, particularly 1.5 mm or more, the wall thickness be 1.0 to 2.5 mm, particularly 1.0 to 2.0 mm, the height be 3 to 6 mm, particularly 4 to 5.5 mm, and the inner diameter / outer diameter ratio be 0.17 to 0.67, particularly 0.27 to 0.64. In addition, the preferred shape of the alumina carrier of the present invention may be a conventionally known cylindrical shape depending on the application, and is not particularly limited as long as it has at least one hollow hole penetrating in the height direction, such as the alumina carrier disclosed in JP 2017-154051 A.

[0036] The alumina carrier of the present invention may contain Fe2O3 derived from the hydrated alumina raw material as an impurity. In order not to inhibit the activity of the catalyst to be supported and not to increase the amount of by-products produced, the content of Fe2O3 is preferably 400 ppm or less, more preferably 200 ppm or less. The alumina carrier of the present invention also contains a certain amount of metal components derived from the fatty acid metal salt of the raw material, and the amount of the fatty acid metal salt used can be appropriately adjusted depending on the application. In general, the metal components are oxides of alkali metals or alkaline earth metals, and when the alumina carrier of the present invention is used as a carrier for a catalyst for the gas phase chlorination reaction of ethylene, the preferred metal components are oxides of alkaline earth metals. The content of the metal components derived from the fatty acid metal salt relative to the alumina carrier of the present invention is preferably in the range of 0.01 to 5 mass%.

[0037] The alumina support of the present invention is an alumina support used for a catalyst for a gas phase reaction, and is preferably used as a support for a catalyst for the gas phase chlorination reaction of ethylene. There are two types of gas phase chlorination reaction of ethylene: oxychlorination reaction in which ethylene reacts with hydrogen chloride and oxygen, and direct chlorination reaction in which ethylene reacts directly with chlorine. The catalyst using the carrier of the present invention can be used in either reaction type. The more preferred reaction type is when used as a catalyst for oxychlorination reaction of ethylene.

[0038] <Gas phase reaction catalyst> The gas-phase reaction catalyst of the present invention is an alumina carrier of the present invention carrying one or more optional metal compounds as catalytic components. The gas-phase reaction catalyst of the present invention has a high catalytic activity and a low yield of by-products due to the extremely characteristic pore distribution of the alumina carrier of the present invention.

[0039] As a method for supporting a metal compound as a catalytic component, a known method can be adopted, such as an impregnation method in which the alumina carrier of the present invention is immersed in a solution of a soluble salt of the catalytic active component to introduce the compound into the carrier, but it is preferable to use an impregnation method which is easy to operate and convenient for maintaining stable catalytic properties. For example, the alumina carrier of the present invention is preferably immersed in an impregnation solution at room temperature or above room temperature and maintained under conditions in which the desired component is sufficiently impregnated into the carrier. The concentration, amount, temperature, etc. of the impregnation solution can be appropriately adjusted so that the desired amount of the catalytic component is supported.

[0040] The gas phase reaction catalyst on which the metal compound is supported in this manner is suitably packed in a reactor or the like for use.

[0041] As the metal compound, a metal compound containing copper, vanadium, manganese, chromium, molybdenum, tungsten, iron, cobalt, nickel, osmium, platinum, palladium, rhodium, iridium, ruthenium, or the like can be supported. When the gas-phase reaction catalyst of the present invention is used for a gas-phase oxychlorination reaction of ethylene, it is preferable to support a copper compound, particularly copper chloride, among these compounds. Of these, by supporting cupric chloride, the catalyst has high catalytic activity and high retention stability. Furthermore, by adding one or two metal compounds of Group 1 elements of the periodic table (e.g., potassium chloride, cesium chloride, etc.) in addition to copper chloride, the amount of by-products produced can be reduced, i.e., the selectivity to dichloroethane (EDC) can be improved.

[0042] The copper chloride supported catalyst of the present invention is preferably used as a catalyst for the gas phase oxychlorination reaction of ethylene. In the gas-phase oxychlorination reaction of ethylene, ethylene is chlorinated to obtain dichloroethane (hereinafter referred to as "EDC", structure: Cl-CH2-CH2-Cl), with monochloroethane (hereinafter referred to as "EtCl", structure: CH3-CH2-Cl) being generated as a by-product. Catalysts for ethylene oxychlorination are required to have catalytic activity suitable for the reactor and high selectivity to EDC. Catalysts with excessively high catalytic activity usually tend to have low selectivity to EDC. The catalytic activity of the supported copper chloride in the gas-phase oxychlorination reaction of ethylene is preferably 6.0 g-EDC / (cm 3 -catalyst·Hr) or more, preferably 7.0g-EDC / (cm 3 -Catalyst·Hr) or more. The catalytic activity can be controlled by controlling the copper chloride concentration and the total pore (15 to 20,000 nm) volume. The copper chloride concentration is preferably in the range of 10.0 to 18.0% by weight. The total pore (15 to 20,000 nm) volume is preferably in the range of 0.05 to 0.200 cm. 3 / g range is preferred. In addition, the relative selectivity of monochloroethane, which is the main by-product (hereinafter referred to as "by-product selectivity"), is evaluated in terms of the ratio of the amount of monochloroethane produced to the amount of EDC produced (EtCl / EDC), and is preferably 0.4 or less, more preferably 0.35 or less. Here, it is desirable to have a low production ratio of the by-product monochloroethane, which results in a high selectivity to EDC. The by-product selectivity can be controlled by controlling the concentration of added metal salts such as potassium chloride and the volume of macropores (1000 to 20000 nm). The concentration of added metal salts such as potassium chloride is preferably in the range of 1.0 to 7.0% by weight. The volume of macropores (1000 to 20000 nm) is preferably 0.001 to 0.02 cm. 3 / g range is preferred.

[0043] There is no particular restriction on the reaction format when EDC is produced by the oxychlorination reaction, and it can be carried out in any reaction format, for example, in a fixed bed flow type or a fluidized bed flow type. Of these, it is preferable to carry out the reaction in a fixed bed flow type because the apparatus is simple. There is no particular restriction on the reaction format when EDC is produced by the oxychlorination reaction using ethylene, hydrogen chloride and oxygen as raw materials, and it can be carried out in any reaction format, for example, in a fixed bed flow type or a fluidized bed flow type. Of these, it is preferable to carry out the reaction in a fixed bed flow type because the apparatus is simple. There is no particular restriction on the reaction format when EDC is produced by the oxychlorination reaction using ethylene, hydrogen chloride and oxygen as raw materials, and it can be carried out in any reaction format, for example, in a fixed bed flow type or a fluidized bed flow type. Of these, it is preferable to carry out the reaction in a fixed bed flow type because the apparatus is simple. There is no particular restriction on the reaction format when EDC is produced by the oxychlorination reaction using ethylene, hydrogen chloride and oxygen as raw materials, and it can be carried out in any reaction format, for example, in a fixed bed flow type or a fluidized bed flow type. Among these, the fixed bed flow system is preferred because the apparatus required is simple.

[0044] The catalyst for oxychlorination of the present invention is characterized in that it exhibits very high selectivity to EDC despite its high pressure resistance. As for the shape of the fixed-bed oxychlorination catalyst, a hollow cylindrical shape is preferred from the viewpoints of not only reducing the pressure loss but also improving the selectivity for EDC, as described above with respect to the alumina carrier. Since the gas-phase oxychlorination reaction of ethylene is an exothermic reaction, the accumulation of heat in the catalyst tends to generate a large amount of by-products other than EDC. To avoid this, it is preferable to make the height of the catalyst body smaller. On the other hand, if the height is made too small, it will lead to the catalyst cracking and powdering, so it is preferable to make the thickness small while maintaining the pressure resistance strength of the hollow cylindrical shape.

[0045] The pressure resistance of the catalyst for oxychlorination process according to the present invention is an average pressure resistance of 18 N or more, preferably 20 N or more. If the pressure resistance is 18 N or more, the catalyst is hardly broken or pulverized when it is packed into a reactor. In addition, the catalyst is hardly broken or pulverized during operation in the reactor. Here, resistance to destruction and powdering in the reactor is a desirable catalyst property, since it suppresses an increase in the differential pressure in the reactor.

[0046] <Method of manufacturing alumina carrier> The method for producing an alumina carrier of the present invention is characterized in that it comprises preparing a hydrated alumina having at least two particle size distribution peaks in a particle size region of 300 μm or less, mixing the hydrated alumina with a fatty acid metal salt to prepare a raw material for molding, compression molding the raw material for molding to obtain a cylindrical body having at least one hollow hole passing therethrough, and calcining the cylindrical body to convert the hydrated alumina (aluminum hydroxide) into alumina (aluminum oxide).

[0047] The hydrated alumina has at least two peaks in the particle size distribution in the region of particle size of 300 μm or less, and preferably has three or more peaks in the particle size distribution in the region of particle size of 300 μm or less. In addition, it is preferable that the peak apex of the particle size distribution is in two or more of the ranges of 0.1 μm or more and less than 1.0 μm, 1.0 μm or more and 10.0 μm or less, and 100 μm or more and 300 μm or less, and it is particularly preferable that the particle size distribution has at least one peak apex in all three ranges. It is advantageous for the hydrated alumina used in the production of the alumina carrier of the present invention to have at least two peaks of the particle size distribution as described above in order to form a multi-pore structure. In addition, the broader the width of each peak, the higher the catalytic activity and the lower the yield of by-products.

[0048] It is preferable to use pseudo-boehmite as the hydrated alumina. That is, by firing pseudo-boehmite, alumina, preferably alumina having a γ-type structure or a structure close to a γ-type structure, can be obtained, for example, with a BET specific surface area of ​​140 to 280 m. 2 This is because alumina with a large BET specific surface area, such as 0.1 μm / g, can be obtained.

[0049] The hydrated alumina is preferably in the form of a powder for the convenience of filling the molding machine. 50 ) is 45 to 100 μm, D 10 is 1 to 10 μm, D 90 The median diameter (D 50 ) and D 10 , D 90 If it is not within the above range, there is a risk that the pore distribution unique to the alumina carrier of the present invention will not be obtained.

[0050] The hydrated alumina preferably has a moisture content of 20% by mass or less, particularly 15% by mass or less. If the moisture content exceeds 20% by mass, there is a risk that cracks will easily occur during firing.

[0051] The fatty acid metal salt, which is the raw material of the alumina molded body of the present invention, is blended for the purposes of reducing friction during compression molding and forming pores in the alumina carrier by volatilizing it during firing. The fatty acid metal salts include magnesium stearate, calcium stearate, sodium stearate, potassium stearate, etc. Among these, magnesium stearate is preferably used in the present invention.

[0052] The amount of the fatty acid metal salt added is preferably 2 to 7 mass %, and more preferably 3 to 6.5 mass %, based on the amount of the hydrated alumina used as the raw material. If the amount of the fatty acid metal salt added is less than 2% by mass, the hydrated alumina may stick to the compression molding machine, resulting in a significant decrease in productivity, whereas if the amount of the fatty acid metal salt added is more than 7% by mass, the number of macropores of 1000 nm to 20000 nm may increase, resulting in insufficient reduction in by-products.

[0053] Furthermore, as the raw material for the alumina molded body of the present invention, if necessary, an inorganic excipient or binder may be used, such as a powder of a kaolin group clay mineral, such as kaolin, halloysite, kibushi clay, or gairome clay, a montmorillonite group clay mineral, such as montmorillonite, bentonite, or beidellite, or a trioctahedral layer type clay mineral, such as saponite, stevensite, or hectorite, in an amount of 50% by mass or less, preferably 2 to 10% by mass, based on the hydrated alumina.

[0054] According to the present invention, the above-mentioned raw materials are mixed to prepare a raw material for molding, and the mixture is compression molded and heat treated to obtain an alumina molded body. For mixing the raw materials, a known mixer such as a conical blender, a ribbon blender, or a Henschel mixer can be used.

[0055] For compression molding, a known molding machine is used. The molding machine generally has a die having a pestle corresponding to the formation of a through-hole, and is, for example, a combination of a die (a cylindrical die), an upper pestle (a piston that pressurizes the raw material from above the die), and a lower pestle (a piston that pressurizes the raw material from below the die), and is configured as follows: (1) Filling: The upper punch rises and the lower punch descends to supply the raw powder into the mortar. (2) Compression: The upper punch descends, or the lower punch ascends to compress the raw material powder in the mortar. (3) Release: The upper punch rises, and the lower punch also rises to release the compression-molded body from the die. (4) Preparation: The lower punch descends and returns to the filling state. The compression molding is carried out by the above-mentioned method.

[0056] In the above-mentioned (1) charging, the supply of the raw material powder into the die may be promoted by supplying air or the like.

[0057] When we look at the behavior of powder during compression molding, the voids in the powder gradually decrease and the particles become closely attached to each other to form a mold; this process is said to go through the following four stages: Stage 1: The raw material particles slide against each other, filling voids and increasing density. Second stage: As the pressure increases further, the bridges within the powder are broken down, the voids are filled, and the raw material itself begins to deform. Third stage: Part of the particle breaks down, creating new surfaces that form a tight bond. Fourth stage: The work hardening of the raw material particles reaches its limit, and even if further pressure is applied, no volume change occurs, and the forming is completed. In practice, these four stages are not clearly distinguished and may occur partially simultaneously. However, the raw material mixture (raw material for molding) used in the present invention is a mixture of the above-mentioned hydrated alumina and fatty acid metal salt, and therefore has excellent compression moldability and is molded homogeneously and with a high yield.

[0058] The raw material mixture (raw material for molding) used in the present invention can be molded using a single shot compression molding machine, but it is preferable to use a continuous or rotary compression molding machine. In this continuous or rotary compression molding machine, for example, a large number of compression molding units each consisting of a combination of the mortar, the upper punch, and the lower punch are arranged around a rotating turret, and as the turret rotates, the steps (1) to (4) are performed in sequence to complete the compression molding.

[0059] The shape and dimensions of the cylindrical body (molded body) having a through-hole obtained by compression molding can be freely selected by changing the shape and dimensions of the punch or mold. When there is one through-hole in the height direction, the position of the hollow hole is preferably one that penetrates the center of the cylindrical body from the viewpoint of strength, and when two or more hollow holes are formed, the position is appropriately adjusted so that the compression strength and abrasion strength are suitable for the intended use.

[0060] In the production of the alumina carrier of the present invention, it is preferable to control the pore structure of the alumina carrier by adjusting the compact density during compression molding. The compact density during compression molding is adjusted by the amount of raw material to be filled and the strength of compression, etc., but in general, when the compact is produced using the continuous or rotary compression molding machine, it is evaluated by the weight per height dimension of the compact. That is, since the outer diameter and inner diameter are fixed by the size of the mold, the mass of the compact per height dimension can be used as a simple index. In addition, since the mass of the compact varies depending on the amount of moisture attached to the raw material, it is preferable to obtain the moisture amount in advance and manage the compact density in terms of the mass dried at 150°C. The density of the compact thus evaluated is preferably 0.016 to 0.024 g / mm, more preferably 0.018 to 0.022 g / mm. If the density of the compact after compression molding is less than 0.016 g / mm, the compressive strength and abrasion strength may be reduced. If the density of the compact after compression molding is more than 0.024 g / mm, the pore volume and specific surface area may be reduced, and the catalytic activity may be reduced.

[0061] According to the present invention, the thus obtained cylindrical body (molded body) having a through-hole is finally fired to obtain an alumina carrier. The firing temperature is preferably 450 to 750°C, more preferably 500 to 700°C, and it is appropriate to perform heat treatment at the above temperature for about 30 minutes to 5 hours. If the firing temperature is less than 450°C, the pressure resistance of the alumina carrier may be insufficient, while if the firing temperature is higher than 750°C, the pore distribution unique to the alumina carrier of the present invention may not be obtained.

[0062] <Production method of dichloroethane using gas phase reaction catalyst> In the method for producing dichloroethane using the catalyst for oxychlorination of the present invention, ethylene, hydrogen chloride and oxygen are used as raw materials, and the reaction is controlled under appropriate temperature and pressure to produce dichloroethane. Instead of oxygen, air or air containing added oxygen can be used. There is no particular limit to the reaction temperature, and in particular, 100°C to 400°C is preferred, and in particular, 150°C to 350°C is preferred, as conversion to EDC is efficient. There is no particular limit to the reaction temperature, and in particular, 100°C to 400°C is preferred, and in particular, 150°C to 350°C is preferred, as conversion to EDC is efficient. There is no particular limit to the reaction temperature, and in particular, 100°C to 400°C is preferred, and in particular, 200°C to 330°C is preferred, as dichloroethane is efficiently produced. The reaction pressure is not particularly limited, but is usually 0.01 to 2 MPa, and preferably 0.05 to 1 MPa, in terms of absolute pressure. In addition, the gas hourly space velocity (GHSV) during the fixed bed flow reaction is preferably 1,000 h because this allows the reaction to efficiently proceed. -1 ~10,000hr -1 , and more preferably 2,000 hours -1 ~8,000hr -1 Here, the gas hourly space velocity (GHSV) is the total amount of gas supplied (m 3 / h) with catalyst loading (m 3 ) and is a value that represents the reaction capacity of the packed catalyst. Here, it is desirable that the catalyst performance be such that a sufficient reaction amount can be ensured even when the GHSV is high.

[0063] The dichloroethane obtained by the process for producing dichloroethane using the catalyst for oxychlorination of the present invention can be further pyrolyzed to obtain vinyl chloride monomer. EXAMPLES

[0064] The present invention will be described in detail below with reference to the following examples, but the present invention is not limited to these examples. The various measuring methods used in the following experiments are as follows.

[0065] (1) Particle size measurement of raw materials; The measurements were carried out by laser diffraction and scattering using Malvern's Mastersizer 3000 and Hydro LV. Water was used as the dispersion medium, the particle refractive index was 1.68, the dispersion medium refractive index was 1.33, and the light scattering model was analyzed using the Mie theory.

[0066] (2) specific surface area, differential pore distribution; The nitrogen adsorption method was used to measure the specific surface area. The specific surface area was analyzed by the BET method from the adsorption side nitrogen adsorption isotherm at a specific pressure of 0.05 to 0.20 at -196°C. The differential pore distribution was determined by analyzing the desorption side nitrogen adsorption isotherm using the BJH method.

[0067] (3) pore volume; The measurement was carried out by mercury intrusion porosimetry using an AutoPore IV 9500 manufactured by Micromeritics. The pore volume of 15 nm to 20,000 nm was measured by using a sample weight of approximately 1.5 g and measuring at a pressure range of 10 psia to 15,000 psia under room temperature atmosphere. The cumulative intrusion volume in the above range was taken as the total pore volume, and the cumulative intrusion volume of 10 psia to 220 psia was taken as the macropores with a pore diameter of 1000 nm to 20,000 nm.

[0068] (4) Log differential pore distribution; The measurements were carried out by mercury intrusion porosimetry using a Micromeritics AutoPore IV 9500. A sample weight of approximately 0.5 g was used, and measurements were carried out in the pressure range of 10 psia to 60,000 psia to obtain the Log differential pore size distribution of 3.6 nm to 20,000 nm.

[0069] (5) Compressive strength; Using an Aiko Engineering tabletop load measuring machine I310D and a 50N load cell, the strength of 20 pieces of alumina carrier in the vertical direction to the side of the cylinder was measured. A load was applied to the side of the cylinder at a load speed of 5mm / min, and the load at which the alumina carrier was crushed was displayed digitally and read. The average value of the 20 pieces was taken as the compressive strength.

[0070] (6) tapping bulk density; 500cm 3 200 g of a sample was placed in a measuring cylinder, and the cylinder was vibrated until the packed volume no longer changed, and the packed volume was read, from which the packed density was calculated.

[0071] (7) Preparation of catalyst for gas-phase oxychlorination of ethylene; 50 g of hollow cylindrical alumina support was dissolved in 9.76 g of cupric chloride dihydrate, 1.94 g of potassium chloride, and 1.94 g of cesium chloride in 25 cm of pure water. 3 The alumina carrier was immersed in a solution of the above for 30 minutes at room temperature. The immersed alumina carrier was taken out and dried at 200°C for 2 hours in an electric furnace. It was then calcined at 350°C for 2 hours to obtain a catalyst. It was confirmed that the amounts of metal compounds supported in the obtained catalyst were 12% by weight of cupric chloride, 3% by weight of potassium chloride, and 3% by weight of cesium chloride. The shape of the catalyst was the same as the size of the alumina support. The quantitative determination of metal compounds was carried out by grinding 3 g of the oxychlorination catalyst in a mill, boiling and dissolving it in concentrated hydrochloric acid, and then diluting it with 100 cm 3 A sample solution was prepared by diluting the solution up to 100%. The metal components were quantified by spraying the sample solution into an atomic absorption spectrophotometer flame analyzer (manufactured by Shimadzu Corporation, product name: AA-7000). The amount of metal compound supported relative to the catalyst weight was calculated from the quantitative results of the metal components.

[0072] (8) Activity evaluation; The reaction test for the production of dichloroethane (EDC) was carried out using a fixed-bed flow-type reactor packed with approximately 3 g of the obtained catalyst and inert glass beads as a catalyst packed bed of approximately 19 cm height in a small nickel cylindrical reactor tube (inner diameter 26 mm). The temperature of the outer jacket of the reactor, which used silicone oil as a heat medium, was set and controlled at 240°C, and the reaction temperature inside the reactor was maintained at about 220 to 270°C to carry out the reaction. The raw material gas was introduced from the top of the reactor and reacted by passing through the catalyst layer, and the reaction gas was discharged from the bottom of the reactor to the outside. At this time, the outlet pressure of the reactor was controlled to 0.4 MPaG in gauge pressure. The flow rates of the raw gases were 150 NL / Hr for hydrogen chloride gas, 81 NL / Hr for ethylene, and 80.3 NL / Hr for air. Here, the unit NL is the volume L (0.001 m) at standard conditions (0°C, 1 atm). 3 ) The gas discharged from the reactor was recovered by condensing it into 2,2,4-trimethylpentane that had been cooled in two stages to -38°C and -45°C. The amount of EDC produced was determined by measuring the EDC concentration in the condensate by gas chromatography, and the amount of monochloroethane, the main by-product, was determined by measuring the concentration in the non-condensable gas by gas chromatography. The condensate was analyzed using a gas chromatograph (manufactured by Shimadzu Corporation, model name GC14B) and using SE30 (product name) manufactured by GL Sciences Inc. as the packing material. The non-condensable gas was analyzed using a gas chromatograph (manufactured by Shimadzu Corporation, model name GC14B) and using PorakQ (trade name) manufactured by Waters Corporation as the packing material. The catalytic activity was calculated from the amount of dichloroethane (EDC) produced per gram of catalyst per hour. The by-product selectivity was evaluated as the ratio of the amount of monochloroethane produced to the amount of EDC produced (EtCl / EDC).

[0073] <Example 1> The particle size distribution has peaks at 0.7 μm, 2.9 μm, and 174 μm, and the median diameter (D 50 ) is 67.7μm, D 10 2.43μm, D 9010 kg of hydrated alumina (pseudo-boehmite) with a particle size of 258 μm and 500 g of magnesium stearate were mixed to prepare the raw material for molding, which was then filled into a mold (mortar) with an outer diameter of 4.8 mm and an inner diameter of 2.2 mm and pressed with upper and lower punches to obtain a compression molded product with a density of 0.0201 g / mm when calculated as the dry mass at 150°C. This was fired at 620°C for 2 hours to obtain an alumina carrier with a γ crystal structure. The alumina carrier had a cylindrical shape with one hollow hole in the center that penetrated in the height direction, and the outer diameter of the circle was 4.5 mm, the inner diameter was 2.0 mm, the wall thickness was 1.25 mm, and the height was 5.0 mm. The EDC activity of the ethylene chlorination catalyst prepared from the alumina support was 7.65 g-EDC / (cm 3 -catalyst·Hr), and the by-product selectivity was 0.30.

[0074] <Example 2> An alumina carrier was obtained by the same operation as in Example 1, except that the compact density calculated as the dried mass at 150°C was 0.0208 g / mm. The alumina carrier had a cylindrical shape as in Example 1, with an outer diameter of 4.5 mm, an inner diameter of 2.0 mm, a wall thickness of 1.25 mm, and a height of 5.0 mm. The EDC activity of the ethylene chlorination catalyst prepared from the alumina support was 6.65 g-EDC / (cm 3 -catalyst·Hr), and the by-product selectivity was 0.31.

[0075] <Example 3> An alumina carrier was obtained by the same operation as in Example 1, except that the compact density calculated as the dried mass at 150°C was 0.0199 g / mm. The shape of the alumina carrier was cylindrical as in Example 1, with an outer diameter of 4.5 mm, an inner diameter of 2.0 mm, a wall thickness of 1.25 mm, and a height of 5.0 mm. The EDC activity of the ethylene chlorination catalyst prepared from the alumina support was 7.13 g-EDC / (cm 3 -catalyst·Hr), and the by-product selectivity was 0.34.

[0076] <Comparative Example 1> There is only one peak in the particle size distribution at the particle size 81 μm position, and the median diameter (D 50 ) is 67.3μm, D 10 21.9, D 90 An alumina carrier having a γ crystal structure was obtained by the same operation as in Example 1, except that hydrated alumina (pseudo-boehmite) with a diameter of 132 μm was used and the compact density converted into a dry mass at 150° C. was set to 0.0200 g / mm. The alumina carrier had a cylindrical shape as in Example 1, with a circular outer diameter of 4.6 mm, an inner diameter of 2.0 mm, a wall thickness of 1.3 mm, and a height of 5.0 mm. The EDC activity of the ethylene chlorination catalyst prepared from the alumina support was 7.84 g-EDC / (cm 3 -catalyst·Hr), and the by-product selectivity was 0.35.

[0077] <Comparative Example 2> An alumina carrier was obtained by the same operation as in Example 1, except that the amount of magnesium stearate was 800 g and the compact density converted into a dry mass at 150° C. was 0.0197 g / mm. The alumina carrier had a cylindrical shape as in Example 1, with an outer diameter of 4.5 mm, an inner diameter of 2.0 mm, a wall thickness of 1.25 mm, and a height of 5.0 mm. The EDC activity of the ethylene chlorination catalyst prepared from the alumina support was 7.03 g-EDC / (cm 3 -catalyst·Hr), the by-product selectivity was 0.35.

[0078] <Comparative Example 3> An alumina carrier was obtained by the same operation as in Comparative Example 2, except that the compact density calculated as the dried mass at 150°C was 0.0196 g / mm. The alumina carrier had a cylindrical shape as in Comparative Example 2, with an outer diameter of 4.5 mm, an inner diameter of 2.0 mm, a wall thickness of 1.25 mm, and a height of 5.0 mm. The EDC activity of the ethylene chlorination catalyst prepared from the alumina support was 7.86 g-EDC / (cm 3 -catalyst·Hr), and the by-product selectivity was 0.42.

[0079] <Comparative Example 4> The particle size distribution has peaks at the particle size positions of 0.7 μm, 2.9 μm, and 48.6 μm, and the median diameter (D 50 ) is 25.1μm, D 10 2.02μm, D 90 An alumina carrier was obtained by the same operation as in Example 1, except that hydrated alumina (pseudo-boehmite) with a diameter of 161 μm was used and the compact density calculated as the dried mass at 150° C. was 0.0151 g / mm. The alumina carrier had a cylindrical shape as in Example 1, with an outer diameter of 4.5 mm, an inner diameter of 2.0 mm, a wall thickness of 1.25 mm, and a height of 4.6 mm.

[0080] The samples obtained in each of the Examples and Comparative Examples were subjected to measurement of physical properties and evaluation of catalytic performance. The results are shown in Table 1.

[0081] [Table 1]

[0082] It is seen from Examples 1 to 3 and Comparative Examples 2 and 3 that an alumina carrier having a pressure resistance of more than 20 N can be obtained by using a raw material having three particle size distribution peaks below 300 μm and a median diameter of 45 to 100 μm. Furthermore, it is seen from Examples 1 to 3 that an alumina carrier having a pressure resistance of more than 20 N can be obtained by reducing the total pore volume to 0.04 cm 3 / g to 0.15cm 3 / g, macropores with pore diameters of 1000 nm to 20,000 nm are 0.02 cm 3 / g or less, the EDC activity is 6.6 g-EDC / (cm 3 While showing high activity of more than 0.1–catalyst·Hr, it also shows high selectivity to EDC with a by-product selectivity of less than 0.35.

Claims

1. An alumina support for use in a catalyst for the gas phase chlorination of ethylene, comprising: It has a cylindrical shape with at least one hollow hole passing therethrough, BET specific surface area is 140 to 280 m 2 / g, The volume of pores with diameters of 15 nm to 20,000 nm measured by mercury intrusion porosimetry is 0.04 to 0.15 cm 3 / g, and the volume of the pores having a diameter of 1000 nm or more and 20000 nm or less is 0.02 cm 3 / g or less, In a differential pore distribution graph obtained from the pore volume measured by a nitrogen adsorption method, the peak apex is located in the range of 3 to 9 nm, An alumina carrier having a tapping bulk density of 620 to 780 g / L.

2. 2. The alumina carrier according to claim 1, having an average compressive strength of 18 N or more.

3. The alumina carrier according to claim 1 or 2, wherein the shape is a cylinder having one hollow hole penetrating in the height direction, the outer diameter of the circle is 3 to 6 mm, the inner diameter is 1.0 mm or more, the thickness is 1.0 to 2.5 mm, and the height is 3 to 6 mm.

4. A gas phase reaction catalyst comprising the alumina carrier according to any one of claims 1 to 3, and one or more metal compounds supported on the carrier.

5. 5. The gas phase reaction catalyst according to claim 4, wherein copper chloride is supported as the metal compound.

6. The volume of pores with diameters of 15 nm to 20,000 nm measured by mercury intrusion porosimetry is 0.04 to 0.15 cm 3 / g, and the volume of pores having a pore diameter of 1000 nm or more and 20000 nm or less is 0.02 cm 3 The gas phase reaction catalyst according to claim 4 or 5, wherein the molecular weight of the catalyst is 1000 or less.

7. 7. The gas phase reaction catalyst according to claim 4, which is used as a catalyst for producing dichloroethane by the gas phase chlorination reaction of ethylene.

8. Using hydrated alumina having at least one peak apex of a particle size distribution in all three ranges of particle size, namely, 0.1 μm or more and less than 1.0 μm, 1.0 μm or more and 10.0 μm or less, and 100 μm or more and 300 μm or less, The hydrated alumina is mixed with a fatty acid metal salt to prepare a raw material for molding; The molding material is compression molded to obtain a cylindrical body having at least one through-hole; calcining the cylinder to convert the hydrated alumina to alumina; The method for producing an alumina carrier according to any one of claims 1 to 3,

9. The hydrated alumina has a median diameter (D 50 ) is 45 to 100 μm, D 10 is 1 to 10 μm, D 90 The method according to claim 8, wherein the thickness is 180 to 400 μm.

10. A method for producing dichloroethane using the catalyst according to any one of claims 4 to 7.

11. A method for producing dichloroethane, comprising reacting ethylene, hydrogen chloride gas and oxygen at 220° C. to 330° C. in the presence of the catalyst according to any one of claims 4 to 7.

12. A method for producing a vinyl chloride monomer, comprising a step of thermally decomposing dichloroethane obtained by the method for producing dichloroethane according to claim 10 or 11.

Citation Information

Patent Citations

  • Catalyst formed in novel cylindrical shape

    JP1981141842A

  • Cylindrical catalyst and manufacture of 1,2-dichloruethane

    JP1992227065A

  • Alumina-based formed body

    JP2001226172A

  • Catalyst for oxychlorination of ethylene to 1,2-dichloroethane in fixed bed

    JP2010149115A

  • Oxychlorination catalyst

    JP2012187569A